A study of the methodological and clinical validity of the combined lactulose hydrogen breath test with scintigraphic oro‐cecal transit test for diagnosing small intestinal bacterial overgrowth in IBS patients. Issue 6 (18th March 2014) - Zhao, J.; Zheng, X.; Chu, H.; Zhao, J.; Cong, Y.; Fried, M.; Fox, M.; Dai, N.
Abstract Background Small intestinal bacterial overgrowth (SIBO) may be a cause of irritable bowel syndrome (IBS); however, current investigations have important limitations. We aimed to identify clinically relevant diagnostic criteria for SIBO based on lactulose hydrogen breath test (LHBT) alone and combined with scintigraphic measurement of oro‐cecal transit (SOCT). Methods Results of LHBT/SOCT investigation from 89 IBS patients and 13 healthy volunteers were included in a systematic analysis of six published criteria for SIBO diagnosis. Clinical relevance of competing criteria was determined by assessing (i) prevalence of SIBO in IBS patients and healthy volunteers (ii) if SIBO diagnosis predicted improvement in IBS symptoms in a prospective, pilot therapeutic trial of a non‐absorbable antibiotic (rifaximin 600 mg b.d.) in IBS patients. Key Results Reproducibility of SIBO diagnosis by combined LHBT/SOCT was near perfect. A ≥5 ppm H2 increase prior to appearance of cecal contrast was detected in more IBS patients than healthy volunteers (35/89 vs 1/13; p = 0.026), but not for other diagnostic criteria. IBS patients with SIBO, compared to those without SIBO, reported significantly greater improvement in abdominal symptoms following rifaximin therapy (p < 0.002 overall IBS symptom severity). This improvement was most marked in D‐IBS patients in whom all symptoms improved, including stool frequency and consistency (all p < 0.004). Conclusions & Inferences Combined LHBT/SOCT testing using a H2 5 ppm cutoff may identify a subgroup of IBS patients with SIBO. Pilot data examining the clinical response to rifaximin suggest that this subset of IBS patients may benefit more than those with a normal test.